Tengger Herbal (concocted) coffee formulation with fennel seed (Foeniculum vulgare) and ginger (Zingiber officinale) extract - Susinggih Wijana; Claudia G. Perdani; Muhammad I. Febrianata; Panji Deoranto (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2019)
Coffee is a drink suitable for consumption in cold areas. Bromo tourist area is a producer of fennel plants that can be used as a drink to warm the body. This study used Robusta coffee, fennel seed and ginger extract as the basic ingredients for making herbal coffee. The study aimed to obtain a herbal coffee formulation based on fennel seed and ginger extract to enhanceand sustain food diversity in Bromo. This study employed the Response Surface Methodology (RSM) method with two factors (i.e. the proportion of Robusta coffee and the proportion of fennel seed and ginger extract) and three responses (i.e. pH, TSS, color L). Selection of the best treatment was carried out by using the effectiveness index method. The best treatmentresults and optimal solutions for RSM were then tested for antioxidant activity by using DPPH method. The results showed that optimal formulation of coffee (based on RSM) in a proportion of Robusta coffee of 12.50 g (proportion of fennel seed and ginger extract of 10.00 g) has a pH of 5.93, total soluble solids of 12.00 °Brix and L value of26.56 with IC 50 value of 75.50 ppm.Whereas, the best organoleptic result was found from the first treatment, in the proportion of 14.00 g Robusta coffee (with fennel seed and ginger extracts of 10.00 g with a pH value of 5.73, total soluble solids of 13.00°Brix, L * value of 25.06 and IC 50 of 69.50 ppm).